Exercise-Induced hyponatremia in ultradistance triathletes is caused by inappropriate fluid retention - Speedy, D. B.; Rogers, I. R.; Noakes, T. D.; Wright, S.; Thompson, J. M.; Campbell, R.; Hellemans, I.; Kimber, N. E.; Boswell, D. R.; Kuttner, J. A.; Safih, S. (Clinical Journal of Sport Medicine, 2000)
OBJECTIVE: To study fluid and sodium balance during overnight recovery following an ultradistance triathlon in hyponatremic athletes compared with normonatremic controls. CASE CONTROL STUDY: Prospective descriptive study. SETTING: 1997 New Zealand Ironman Triathlon (3.8 Km swim, 180 Km cycle, 42.2 Km run). PARTICIPANTS: Seven athletes ("subjects") hospitalized with hyponatremia (median sodium [Na] = 128 mmol L(-1)). Data were compared with measurements from 11 normonatremic race finishers ("controls") (median sodium = 141 mmol L(-1)). INTERVENTIONS: None. MAIN OUTCOME MEASURES: Athletes were weighed prior to, immediately after, and on the morning after, the race. Blood was drawn for sodium, hemoglobin, and hematocrit immediately after the race and the following morning. Plasma concentrations of arginine-vasopressin (AVP) were also measured post race. RESULTS: Subjects were significantly smaller than controls (62.5 vs. 72.0 Kg) and lost less weight during the race than controls (median -0.5% vs. -3.9%, p = 0.002) but more weight than controls during recovery (-4.4% vs. -0.8%, p 0.002). Subjects excreted a median fluid excess during recovery (1,346 ml): controls had a median fluid deficit (521 ml) (p = 0.009). Estimated median sodium deficit was the same in subjects and controls (88 vs. 38 mmol L(-1), p = 0.25). Median AVP was significantly lower in subjects than in controls. Plasma volume fell during recovery in subjects (-5.9%, p = 0.016) but rose in controls (0.76%, p = NS). CONCLUSIONS: Triathletes with symptomatic hyponatremia following very prolonged exercise have abnormal fluid retention including an increased extracellular volume, but without evidence for large sodium losses. Such fluid retention is not associated with elevated plasma AVP concentrations.